International Trade of Isolated Countries: The Case of Myanmar and North Korea - JINHWAN OH (European Regional Science Association (ERSA), 2011)
Using a gravity model, this study examines trade patterns of two isolated economies - Myanmar and North Korea. This study finds that two countries' trade is basically consistent with the prediction of the gravity model. However, economic sanctions toward these countries imposed by the U.S. and other developed countries have distorted their trade pattern, and it turns out that China is exerting its power in place of other santion-participating countries. Relevant policy implications follow.
Keywords: 330